Seroprevalence and mole¬cular detection of Coxiella burnetii among sheep in Egypt - H. F. Kamaly; M. I. Hamed; M. F. Mansy; M. Rushdi (Bulgarian Journal of Veterinary Medicine, 2024)
Q fever has become one of the most common causes of abortion in sheep herds, resulting in signifi-cant financial losses for Egyptian farmers. The goal of this study was to establish Coxiella burnetii seroprevalence and molecular detection in three sheep farms in Egypt. A total of 184 sheep of various ages and sexes had their serum samples and vaginal swabs taken. All serum samples were checked for the presence of C. burnetii antibodies by using an ELISA, while 50 vaginal swabs were randomly chosen for molecular detection of the C. burnetii IS1111 gene. The overall seroprevalence of Q fever in sheep was 37.5%, and it was more common in females (39.5%) than in males (8.3%). Antibodies to C. burnetii were found in more than half of pregnant ewes (47.7%). Antibodies to C. burnetii were found in 47.7% of pregnant ewes, compared to 31.4% in non-pregnant and abortive ewes (43.8%). Seroprevalence was observed to be significantly higher in sheep older than 3 years (71.2%). The presence of the C. burnetii IS1111 gene was found in 20% of the molecularly analysed vaginal swabs. Based on the abortion history and pregnancy state of the studied sheep, no statistical significance was identified, since the C. burnetii gene was present in equal percentages in both aborted and non-aborted ewes. A comparison of ELISA and PCR results for vaginal swab samples revealed a statistically non-significant link between the two procedures’ results. These findings revealed sheep as an important reservoir for C. burnetii infection, implying that the role of C. burnetii in sheep should be studied further.